2019
DOI: 10.1002/14651858.cd012295.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for the prevention of migraine in adults

Abstract: To assess beneficial and adverse effects of psychological treatment versus active alternative treatment or no treatment in adults with migraine, using methods that allow comparison with reviews of psychological interventions for other painful conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 106 publications
0
40
2
4
Order By: Relevance
“…These results underline that patients require specialised treatment to approach all domains of headache-related disability and impaired bio-psycho-social health. Importantly, headache frequency alone did not even show a modest correlation with most of the QoL domains, which additionally highlights the need for specialist care and routine administration of instruments enabling assessment of these domains [5,21]. Specialists can provide access to multi-modal interventions that were shown to provide moderate to strong effect sizes to enhance affective symptoms, QoL and disability [22].…”
Section: Current Studymentioning
confidence: 98%
“…These results underline that patients require specialised treatment to approach all domains of headache-related disability and impaired bio-psycho-social health. Importantly, headache frequency alone did not even show a modest correlation with most of the QoL domains, which additionally highlights the need for specialist care and routine administration of instruments enabling assessment of these domains [5,21]. Specialists can provide access to multi-modal interventions that were shown to provide moderate to strong effect sizes to enhance affective symptoms, QoL and disability [22].…”
Section: Current Studymentioning
confidence: 98%
“…In addition, chronic migraine has a low response to treatments which are routinely provided to patients (e.g., medications such as triptans, non-invasive vagus nerve stimulation, pain management, stress management, biofeedback, cognitive behavioral therapy, relaxation techniques) (Becker, 2017;May & Schulte, 2016). Similarly, psychological interventions, such as cognitive behavior therapy (Martin et al, 2015) and acceptance commitment therapy (Dindo et al, 2020), improve psychological distress (Dindo et al, 2020;Martin et al, 2015;Knowlton et al, 2019) but do not affect migraine and its disability (Sharpe et al, 2019). Thus, treating chronic migraine is a real challenge for clinicians and studies on psychological treatments are warranted (National Institute for Health and Care Excellence, 2015).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…In this case example, WBT was associated with decrease of migraine attacks and disability as well as with improvement of depressive symptoms, well-being, and euthymia. They are promising results since chronic migraine is commonly resistant to pharmaceutical treatments routinely provided in the clinical realm (e.g., triptans, lamotrigine, amitriptyline) (Becker, 2017;Cecchini et al, 2012;May & Schulte, 2016), is often associated to depression (Araki et al, 2019;Bigal & Lipton, 2009), and psychological interventions studied until now have shown disappointing results in term of number of migraine attacks and migraine disability (Sharpe et al, 2019;Wells et al, 2020). Of course, based on the present clinical case, WBT is promising in chronic migraine patients with a history of depression and current depressive symptoms.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…In one randomized trial among young patients (10-17 years old) suffering from chronic migraine, the use of CBT (10 sessions) plus amitriptyline resulted in greater reductions in days with headache and migraine-related disability compared with the use of headache education plus amitriptyline [180]. A recent meta-analysis found that 54% of individuals with migraine reported at least 50% reduction in migraine frequency after psychological therapy, vs. 24% of controls [181]. Because CBT differs substantially from traditional psychotherapy, it focuses on here and now and it is typically time limited; this therapeutic option may help practitioners in migraine management, in pediatric populations in particular [182].…”
Section: Cognitive Behavioral Therapiesmentioning
confidence: 99%